Novel ultrathin double-balloon endoscopy for the diagnosis of small-bowel diseases: a multicenter nonrandomized study - Nakamura, Masanao; Yano, Tomonori; Esaki, Motohiro; Oka, Shiro; Mitsui, Keigo; Hirai, Fumihito; Kawasaki, Keisuke; Fujishiro, Mitsuhiro; Torisu, Takehiro; Tanaka, Shinji; Iwakiri, Katsuhiko; Kishi, Masahiro; Matsumoto, Takayuki; Yamamoto, Hironori (Endoscopy, 2020)
Background This study aimed to compare the markers of potential pancreatic injury during antegrade double-balloon endoscopy (DBE) using the newly developed ultrathin EN-580XP system and the conventional EN-580T system.Methods Patients who were scheduled for antegrade DBE during daily clinical practice were enrolled. Clinical background, adverse events, and laboratory data of patients were compared between those who underwent endoscopy using the EN-580XP system and those in whom the EN-580T system was used. The primary end points were pancreatic hyperamylasemia and hyperlipasemia after DBE.Results A total of 295 cases were registered. Pancreatic hyperamylasemia occurred in 2 of 92 patients (2.2 %) in the EN-580XP group and in 28 of 147 patients (19.1 %) in the EN-580 T diagnosis group (P < 0.001). Hyperlipasemia was significantly different between the two groups (1.1 % [EN-580XP] vs. 13.6 % [EN-580 T diagnosis]; P < 0.001). Acute pancreatitis occurred in four patients (7.1 %) in the EN-580 T therapy group. Multiple logistic regression analyses revealed that the endoscope type EN-580 T was significantly associated with pancreatic hyperamylasemia (adjusted odds ratio [OR] 8.63, 95 % confidence interval [CI] 1.97 – 37.70; P < 0.01) and hyperlipasemia (adjusted OR 13.10, 95 %CI 1.70 – 100.70; P = 0.01).Conclusions The EN-580XP system seemed less harmful to the pancreas during antegrade DBE.